2017
DOI: 10.1371/journal.pone.0171122
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Elastic Net with Regression Coefficients Method for Variable Selection of Spectrum Data

Abstract: Using the spectrum data for quality prediction always suffers from noise and colinearity, so variable selection method plays an important role to deal with spectrum data. An efficient elastic net with regression coefficients method (Enet-BETA) is proposed to select the significant variables of the spectrum data in this paper. The proposed Enet-BETA method can not only select important variables to make the quality easy to interpret, but also can improve the stability and feasibility of the built model. Enet-BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…It has been shown that PLSR tends to shrink the low-variance predictors but can also inflate the high-variance predictors, making it unstable and yielding a higher prediction error than penalized regression ( 46 48 ). In high dimensions, when the number of predictors is much greater than the sample size, elastic net has been shown to yield more accurate results than PLSR ( 48 50 ). TimeSignature’s ability to achieve high accuracy using only two samples from an individual with great flexibility in timing (8–12 h apart) using a complement of only 40 genes is a significant advance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PLSR tends to shrink the low-variance predictors but can also inflate the high-variance predictors, making it unstable and yielding a higher prediction error than penalized regression ( 46 48 ). In high dimensions, when the number of predictors is much greater than the sample size, elastic net has been shown to yield more accurate results than PLSR ( 48 50 ). TimeSignature’s ability to achieve high accuracy using only two samples from an individual with great flexibility in timing (8–12 h apart) using a complement of only 40 genes is a significant advance.…”
Section: Discussionmentioning
confidence: 99%
“…ENET shrinks the coefficients of redundant spectral variables to zero, by combining L 1 -norm penalty (lasso) and L 2 -norm penalty (ridge) together [27,28], and then the nonzero spectral variables were considered as effective wavelength variables. Compared with PLS with regression coefficient, elastic net with regression coefficient (named ENET) is more stable and reliable.…”
Section: Spectral Variable Selection Techniquesmentioning
confidence: 99%
“…CARS method generally can obtain satisfactory model accuracy and has become a common method in variable selection techniques [17,[23][24][25][26]. In contrast to partial least squares (PLS) with regression coefficient, elastic net (ENET) with regression coefficient represents a novel variable selection technique, which belongs to the method of regression coefficients of the first group [27,28]. Unlike the PLS probably containing the uninformative variables, ENET can effectively shrink the model coefficients of redundant variables to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Lasso penalty expects many coefficients close to zero, and only a small subset to be larger and none zero [5]. Whether 147 there are a group of variables with high multicollinearity, lasso will select only one variable without caring which one is selected [6]. Elastic net simultaneously selects the variables automatically with continuous shrinkage and has the property to select groups of correlated variables.…”
Section: Introductionmentioning
confidence: 99%
“…It shrinks the regression coefficients by combining L1-norm penalty and L2-norm penalty together. The elastic net identify a higher number of correctly influential variables than the lasso technique, and has lower false positive rate than ridge regression [6,7]. The instability of the lasso regression technique when independent variables are highly correlated as in SNPs in high linkage disequilibrium is overcome using the elastic net that was proposed for analyzing high dimensional data [5].…”
Section: Introductionmentioning
confidence: 99%